Effects of an Advocacy Trial on Food Industry Salt Reduction Efforts—An Interim Process Evaluation - Helen Trevena (Nutrients, 2017)
The decisions made by food companies are a potent factor shaping the nutritional quality of the food supply. A number of non-governmental organizations (NGOs) advocate for corporate action to reduce salt levels in foods, but few data define the effectiveness of advocacy. This present report describes the process evaluation of an advocacy intervention delivered by one Australian NGO directly to food companies to reduce the salt content of processed foods. Food companies were randomly assigned to intervention (n = 22) or control (n = 23) groups. Intervention group companies were exposed to pre-planned and opportunistic communications, and control companies to background activities. Seven pre-defined interim outcome measures provided an indication of the effect of the intervention and were assessed using intention-to-treat analysis. These were supplemented by qualitative data from nine semi-structured interviews. The mean number of public communications supporting healthy food made by intervention companies was 1.5 versus 1.8 for control companies (p = 0.63). Other outcomes, including the mean number of news articles, comments and reports (1.2 vs. 1.4; p = 0.72), a published nutrition policy (23% vs. 44%; p = 0.21), public commitment to the Australian government’s Food and Health Dialogue (FHD) (41% vs. 61%; p = 0.24), evidence of a salt reduction plan (23% vs. 30%; p = 0.56), and mean number of communications with the NGO (15 vs. 11; p = 0.28) were also not significantly different. Qualitative data indicated the advocacy trial had little effect. The absence of detectable effects of the advocacy intervention on the interim markers indicates there may be no impact of the NGO advocacy trial on the primary outcome of salt reduction in processed foods.